Accessory renal artery: A case report and literature review - Abdelmotalab, Mohammed Abdelsalam; Ahmed, Whbat A.M. (مجلة الجزيرة للعلوم الصحية; مجلد 17 عدد 1 (2021), 2022)
Introduction: Variations of renal arteries were most frequent anatomical variation. Moreover, they have clinical implications in surgery and radiology. Case report: During the dissection of approximately 50 year old male cadaver abdomen for undergraduate student, a unilateral right accessory renal artery was observed arising from the lateral side of the abdominal aorta below the origin of the right main renal artery. Conclusion: Knowledge of accessory renal arteries has great importance in the field of surgery, radiology and renal transplantation